Did Tough Antitrust Enforcement Cause the Diversification of American Corporations? - Matsusaka, John G. (Journal of Financial and Quantitative Analysis, 1996)
This paper investigates the hypothesis that tough antitrust enforcement in the 1960s led firms to engage in diversification programs by preventing them from growing within their own industries. If true, diversification should have occurred more often when large firms merged than when small firms merged because small mergers were less likely to have received antitrust attention. Such a pattern is not observed in a sample of 549 acquisitions from 1968?diversification was equally common in large and small mergers. Survey evidence shows that diversification movements occurred in other industrialized nations where there was a loose antitrust environment. Both pieces of evidence suggest that antitrust played a minor role in the diversification movement.